EVALUACIÓN DE LA HABILIDAD COMPRENSIÓN AUDITIVA DE ESPAÑOL COMO LENGUA MATERNA EN ESTUDIANTES DE EDUCACIÓN SECUNDARIA EN LA CIUDAD DE CONCEPCIÓN. - Tapia-Ladino, Monica; Bernales, Nathalie Ariz (Trabalhos em Lingüística Aplicada)
As a difference from the other three language skills (reading, writing and speaking) listening is an ongoing activity, we are always listening. The ability of auditory comprehension has received scarce attention from teachers and researchers. Therefore, this study revises and delimits this concept from others with which it has close relation: listening comprehension, reading comprehension and listening. In turn, the results of a listening test (PCAELM) are presented, which objective is to evaluate the ability regarding different and common oral texts in the media, like: spots, publicity and news. Four levels of listening comprehension are proposed: a first level associated to the superficial comprehension of the text, a second and third level related to local and global inferences respectively, and also a fourth level which to the critical interpretation of the information. 80 students, of the only two-secondhigh school classes of a public school, participated in the application of the test. The results indicate that the gender discourse is not a crucial variable at the moment of understanding a text, however at the levels of listening comprehension proposed by this research, there is evidence of differences. The questions associated with the superficial level of listening comprehension and those related to the purpose of the text are the one that present a better performance as a difference with the ones related with the capacity to make local and global inferences.